2001
DOI: 10.1136/adc.85.6.478
|View full text |Cite
|
Sign up to set email alerts
|

De novo malignancy after paediatric renal replacement therapy

Abstract: Aims-To determine frequency, type, determinants, and outcome of malignancies in children with end stage renal failure. Methods-All Dutch patients, aged less than 15 years, who started chronic renal replacement therapy between 1972 and 1992 and who were at least 18 years old on 1 January 1997, were retrospectively studied. Results-Mean follow up from first renal replacement therapy was 15.5 years. Twenty two malignancies were found in 21 of 249 patients. Skin cancer accounted for 59% and non-Hodgkin lymphoma fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 17 publications
2
51
1
Order By: Relevance
“…Patients who needed .3 consecutive months of RRT were considered to receive chronic RRT. In 2000, we conducted the first study on these 249 patients (9). In 2010, the 10-year extension study was performed, covering the period from the last chart review in 2000 to the last chart review in 2010 or the patient's death.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients who needed .3 consecutive months of RRT were considered to receive chronic RRT. In 2000, we conducted the first study on these 249 patients (9). In 2010, the 10-year extension study was performed, covering the period from the last chart review in 2000 to the last chart review in 2010 or the patient's death.…”
Section: Methodsmentioning
confidence: 99%
“…To this end, LERIC Study coworkers visited all 37 hospitals that had been involved in the medical care of study patients. Data collection of the first period up to 2000 has been described in detail (9). For the second follow-up period, we reviewed the medical charts of all patients between June 1, 2010 and February 1, 2011.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, six new skin cancers were found, which has not earlier been reported after adjuvant chemotherapy of breast cancer, because benign skin tumours are not perhaps counted. Coutinho et al [19] and other authors reported that squamous cell carcinomas, basal cell carcinomas of the skin and non-Hodgkin lymphomas are significantly increased after renal replacement therapy. Detecting two meningiomas after adjuvant CNF is surprising.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated incidence of de novo malignancy is 20% after 10 years and almost 30% after 20 years of chronic immunosuppression. Death is due to various diseases, such as lymphoma/post-transplant lymphoproliferative disease (PTLD), skin cancers, and various solid organ tumor types (1,(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%